2015
DOI: 10.1088/0268-1242/30/5/055011
|View full text |Cite
|
Sign up to set email alerts
|

Double-gate junctionless transistor model including short-channel effects

Abstract: This work presents a physically based model for double-gate junctionless transistors (JLTs), continuous in all operation regimes. To describe short-channel transistors, short-channel effects (SCEs), such as increase of the channel potential due to drain bias, carrier velocity saturation and mobility degradation due to vertical and longitudinal electric fields, are included in a previous model developed for long-channel double-gate JLTs. To validate the model, an analysis is made by using three-dimensional nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 29 publications
(42 reference statements)
0
12
0
2
Order By: Relevance
“…This method has already been used for short channel 2G JNTs [24] and aims to describe the fact that the effective potential that reaches the source, gate and drain in short channel transistors is higher than in longer ones. The increase of the minimum potential in short channel devices is expressed by calculating an effective gate voltage (V GS,eff = V GS + φ min ) and the drain current is calculated by…”
Section: Short Channel Triple-gate Junctionless Nanowire Transistormentioning
confidence: 99%
See 2 more Smart Citations
“…This method has already been used for short channel 2G JNTs [24] and aims to describe the fact that the effective potential that reaches the source, gate and drain in short channel transistors is higher than in longer ones. The increase of the minimum potential in short channel devices is expressed by calculating an effective gate voltage (V GS,eff = V GS + φ min ) and the drain current is calculated by…”
Section: Short Channel Triple-gate Junctionless Nanowire Transistormentioning
confidence: 99%
“…The expression to calculate the saturation drain voltage for long channel transistors (V GT ) is not valid to short channel devices, because they saturate earlier due to higher lateral electric field, responsible for accelerating the carriers, which reach the saturation velocity before V GT , leading the drain current to saturate at lower values of V DS . For JNTs with L b 300 nm the following semi-empirical expression was obtained after multiple simulations [24]:…”
Section: Short Channel Triple-gate Junctionless Nanowire Transistormentioning
confidence: 99%
See 1 more Smart Citation
“…Using the long‐channel approximation, analytical models including charge‐based potential, full range current model, variation of the threshold voltage caused by random dopant fluctuations, and technological constrains and design limitations have been investigated and developed for JL MOSFETs. Also, using the minimum central potential, the threshold voltage shift and the subthreshold slope for symmetric JL MOSFETs working in depletion and accumulation conditions have been determined and compared with the experimental results …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, by reducing the contacts' separating region, it is possible to get higher ON-OFF switching performance. Despite that several experimental and numerical studies published recently have shown the superior fabrication process properties provided by the junctionless device in comparison with the conventional one [4][5][6], the junctionless structure is more vulnerable to the impact of the source/drain parasitic resistance compared to an inversion mode structure [7,8]. The high series resistance associated to the source and drain regions can arise as a serious problem when dealing with uniformly doped channel, which leads to the degradation of the device performance.…”
Section: Introductionmentioning
confidence: 99%